KEBIJAKAN MORATORIUM PEMANFAATAN GAMBUT: POTENSI MANFAAT EKONOMI DAN LINGKUNGAN UNTUK HUTAN TANAMAN INDUSTRI - Arif Prabawa Widiatma (Jurnal Analisis Kebijakan Kehutanan, 2019)
Plantation forest (PF) means to increase land productivity, generate exchange, labor, and industrial materials needs. The issue of climate change and emissions reduction targets caused Government regulated peatland utilizations. It’s necessary to know the economic and environmental benefits of implementing the moratorium policy. The Environmental Accounting approach used to count the benefits, the land value and environment services are valued. As a result, peat has a potential land value IDR 8.5 million/ha, however the changes peatland to PF caused emissions worth Rp40 million/ha. While if peat saturated, peats can control potensial damaged from floods worth US$4/ha and form fire at US$1,000/ha. The economic value of peatland utilization obtained from HTI far less than the potential environmental benefits if it is maintained and saturated. The moratorium policy on limiting changes in peat land use must continue due regard the continuing business of the permit holder whose land is affected by the policy.